2016
DOI: 10.1002/chem.201601145
|View full text |Cite
|
Sign up to set email alerts
|

New External Calibration Curves (ECCs) for the Estimation of Molecular Weights in Various Common NMR Solvents

Abstract: New external calibration curves (ECCs) for the estimation of aggregation states of small molecules in solution by DOSY NMR spectroscopy for a range of different common NMR solvents ([D6 ]DMSO, C6 D12 , C6 D6 , CDCl3 , and CD2 Cl2 ) are introduced and applied. ECCs are of avail to estimate molecular weights (MWs) from diffusion coefficients of previously unknown aggregates. This enables a straightforward and elaborate examination of (de)aggregation phenomena in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 19 publications
2
59
0
3
Order By: Relevance
“…The results of the 1 H-DOSYexternalc alibration curve (ECC) molecular weight( MW)e stimation [49][50][51] used to clarify the structures of 4-7 in solution are discussed in detail below.P revious studies showed that for most organometallic compounds the dissipated spheres and ellipsoids (DSE) calibration curve is the most suitable for an accurate estimation. [52] Therefore, only values from the DSE and, for comparison, from the merge calibrationc urve are considered ( Table 3).…”
Section: Dosy Investigationsmentioning
confidence: 99%
“…The results of the 1 H-DOSYexternalc alibration curve (ECC) molecular weight( MW)e stimation [49][50][51] used to clarify the structures of 4-7 in solution are discussed in detail below.P revious studies showed that for most organometallic compounds the dissipated spheres and ellipsoids (DSE) calibration curve is the most suitable for an accurate estimation. [52] Therefore, only values from the DSE and, for comparison, from the merge calibrationc urve are considered ( Table 3).…”
Section: Dosy Investigationsmentioning
confidence: 99%
“…Die Anwesenheit zweier Maxima in der Elektronendichteverteilung entlang des N Ligand ···O Wasser -Vektors zeigt dabei das Vorliegen einer Wasserstoffbrücke mit Doppelpotential an. [41][42][43] Vorangegangene Studien zeigten, dass bei Verwendung der DSE-Kalibrierungskurve ("dissipated spheres and ellipsoids") die zuverlässigsten Ergebnisse füre ine akkurate Gewichtsabschätzung der meisten organometallischen s-Block-Verbindungen erhalten werden. [36] In diesem Zusammenhang wurde bemerkenswerterweise auch über ein vermeintlich hydrolyseempfindliches Phenylen-1,4bis(trifluoroborat)-Kalium-Doppelsalz berichtet, in dem ein ebenfalls cokristallisiertes Wassermoleküld urch K···O-und OH···p-Wechselwirkungen entscheidend zur Fähigkeit der Selbstorganisation des Moleküls im Festkçrper beiträgt.…”
unclassified
“…[38,39] Die entsprechenden K(1)-O 18-crown-6 -Abstände in einem Bereich zwischen 2.788(1) und 2.935(1) sind ebenso in guter Übereinstimmung zu einem gemittelten Wert von 2.84(8) ,d er fürv erwandte Strukturfragmente in der Cambridge Structural Database gefunden werden kann (1061 Strukturen mit R 0.075). [40] Wiezuerwarten war, zeigt das 1 [41][42][43] Vorangegangene Studien zeigten, dass bei Verwendung der DSE-Kalibrierungskurve ("dissipated spheres and ellipsoids") die zuverlässigsten Ergebnisse füre ine akkurate Gewichtsabschätzung der meisten organometallischen s-Block-Verbindungen erhalten werden. [44]…”
unclassified
“…The diffusion coefficients [ D (comp.)] were corrected by using the signals of [D 7 ]THF as an internal standard, and these corrected coefficients [ D corr (comp.)] were converted by Equation (1) into the corrected estimated molecular masses M corr (comp.)…”
Section: Resultsmentioning
confidence: 99%